High-activity mesoporous Pt/Ru catalysts for methanol oxidation - Franceschini, Esteban Andrés (2013)
High activity mesoporous Pt/Ru catalysts with 2D-hexagonal structure were synthesized using a triblock poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) copolymer (Pluronic F127) template. The normalized mass activities for the methanol oxidation reaction (MOR) of the Pt/Ru catalysts with a regular array of pores is higher than those reported for nanoparticulated Pt/Ru catalysts. Different kinetic parameters, as Tafel slope and activation energy, were obtained for the MOR on the mesoporous catalysts. Results indicated that catalysts performance depends on pore size. Mass activities and the CO2 conversion efficiency for large pore size mesoporous catalysts (10 nm) are greater than those reported for smaller pore size mesoporous catalysts with similar composition. The effect of pore size on catalysts performance is related to the greater accessibility of methanol to the active areas inside large pores. Consequently, the overall residence time of methanol increases as compared with mesoporous catalyst with small pores.